The Analysis of The Corrosion Products of The External X70 Pipeline: Sea and River Water Environment - Johari, Siti Hazirah; Embong, Zaidi (Enhanced Knowledge in Sciences and Technology, 2023)
This study mainly characterized the corrosion products that formed on the X70 pipeline steel's external surface following immersion in sea and river water for several periods. This was mostly attributable to an understanding of the huge impact of corrosion on the X70 pipeline, which is used to transport crude oil, natural gas, and more in the oil and gas industry. Pipeline corrosion can degrade pipeline surfaces, cause leaks, and harm workers in the oil and gas industry. Hence, the main objectives of this research are to determine the chemical and physical properties of sea and river water in order to observe its reaction on the pipeline surface, to characterize the corrosion product properties and its corrosion rate that formed on the X70 pipeline using SEM-EDX, FESEM, XRD, the DSX100 Opto-Digital Microscope, and weight loss analysis to measure corrosion rate, and lastly, to compare the pre- and post-corrosion product and its effect on the pipeline following an immersion test in sea and river water. The seawater and river water locations were chosen by considering the safety of the on-going experiment and the distance to the experimental work done. Furthermore, in this experimental research, six specimens were subjected to exposure. The weight loss analysis was done for all 7 specimens before and after immersion. FESEM and XRD were fully utilized to study the corrosion products and their behaviour by looking at the surface morphology and chemical compounds. Overall, the corrosion rate of X70 immersed in river water was slightly higher compared to X70 immersed in seawater. Consequently, the weight loss of X70 in river water is higher than the weight loss of X70 in seawater due to the different corrosion rates in surface deterioration and degradation. On the whole, based on the data obtained, the corrosion products that formed after the surface morphology analysis were mostly lepidocrocite (γ-FeOOH), goethite (α-FeOOH), hematite (Fe₂O₃) and magnetite (Fe₃O₄).